2007
DOI: 10.4067/s0034-98872007001200003
|View full text |Cite
|
Sign up to set email alerts
|

Detección de lesiones preneoplásicas gástricas mediante niveles séricos de pepsinógeno en población chilena

Abstract: Background: Gastric cancer has a direct relation with chronic atrophic gastritis (AG) and intestinal metaplasia (IM), considered as preneoplastic lesions. Determination of serum pepsinogen I levels (PGI) and pepsinogen I / pepsinogen II ratio (PGI/PGII) can detect this conditions; achieving 70-90% of gastric cancer detection in early stages. Aim: To determine the cutoff values for serum PGI and PGI/PGII in chilean subjects, for the detection of gastric preneoplastic lesions, establishing their sensitivity, spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Zagari et al (264) analyzed 20 studies involving 4,241 participants and found that the sensitivity for diagnosing atrophic gastritis in the gastric body and antrum was 70.4% and 65.4%, respectively. However, few studies to date have measured the levels of pepsinogens for diagnosing gastric atrophy in Latin America (265) and Brazil (266) . Therefore, well-designed studies with a large sample size are necessary to define the performance of this panel in this region.…”
Section: Statement 19 Serological Analysis Of Gastric Atrophy Using Pmentioning
confidence: 99%
“…Zagari et al (264) analyzed 20 studies involving 4,241 participants and found that the sensitivity for diagnosing atrophic gastritis in the gastric body and antrum was 70.4% and 65.4%, respectively. However, few studies to date have measured the levels of pepsinogens for diagnosing gastric atrophy in Latin America (265) and Brazil (266) . Therefore, well-designed studies with a large sample size are necessary to define the performance of this panel in this region.…”
Section: Statement 19 Serological Analysis Of Gastric Atrophy Using Pmentioning
confidence: 99%
“…There are still few studies that relate levels of pepsinogens to the diagnosis of gastric atrophy in Latin America countries (31,32) . The aim of this study was to perform a prospective study to evaluate the concordance between OLGA and OLGIM systems, as well as GastroPanel ® performance in patients with premalignant lesions secondary to H. pylori chronic gastritis in Brazil.…”
Section: Introductionmentioning
confidence: 99%